PENGARUH PENGGUNAAN METODE DISKUSI TERHADAP AKTIVITAS BELAJAR PELAJARAN SOSIOLOGI X SMA NEGERI 2 PONTIANAK - Maharani, Maharani; Ulfah, Maria; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the use of discus methods on student learning activities in SMA Negeri 2 Pontianak. For the use of discussion method of 95.61% of respondents chose very good category and student learning activities of 89.47% of respondents chose very good category, The method used in this research is descriptive method with the form of research relationship studies. Then the population in this study is the students of class X SMA Negeri 2 Pontianak which amounted to 114 students. Data collection techniques in this study using direct techniques, indirect techniques and documentary study techniques. While to analyze the data the researcher uses SPSS version 23.0 statistical program with the result of data analysis of its influence in view from the test sign test with asymp sig 0.000 <0,05 which means there is influence of the use of discussion method to student learning activity in class,it is also found in the recapitulation of answers ti the questionnaire distribution where students tend to answer â€œAâ€(very satisfactory) and â€œBâ€(satisfactory) in the questionnaire.Â Keywords: Discussion Methods, and Learning Activities